Shaping expectations, losing flexibility: A study of CEO promises as strategic communication tools - Majzoubi, Majid; Murray, Alex; Mayew, William J. (Strategic Management Journal, 2026)
Research Summary CEO promises are powerful but understudied communication tools. We develop a dual‐mechanism framework theorizing that while CEO promises elevate stakeholder expectations, they simultaneously constrain strategic flexibility. We argue that CEO promise‐making is shaped by two competing pressures: making more promises when the need to manage expectations upward is heightened and fewer promises when the need to preserve flexibility is increased. Further, we predict that under heightened uncertainty, CEOs preserve flexibility through strategic ambiguity (i.e., issuing promises with extended or vague time horizons and lower specificity). Leveraging Large Language Models (LLMs) to analyze over 69,000 earnings‐call transcripts from S&P 1500 firms (2010–2022), we identify 74,017 CEO promises and find support for our predictions. We contribute an original, publicly available dataset of CEO promises. Managerial Summary When CEOs publicly promise positive future results, they shape how investors and analysts view the company. These promises are a double‐edged sword: they can boost investor and stakeholder confidence, but they also lock the company into a pre‐determined path and make later shortfalls or pivots reputationally costly. Analyzing more than 69,000 earnings calls (2010–2022), we find that CEOs make more promises when needing to prove their legitimacy, such as during early tenure, when facing gender bias, or after missing earnings targets. However, in uncertain environments, CEOs often pull back from promise‐making or employ “strategic ambiguity” by making promises with vaguer timelines and details to maintain flexibility. Our analysis suggests that failing to deliver on these public commitments significantly increases the likelihood of CEO dismissal.